Probabilistyczny Model Sopla Lodu - Wierzbicki, W. (Engineering Transactions, 1957)
It has been found that an icicle hanging from a roof may be considered, with water drops falling from one point, as a durable image of distribution of balls in Galton's device and, with water drops falling from several points, as a durable image of distribution of balls in a device for summing up the relative frequencies of a set of identical random variables. In order to show this, a device for summing up of a set of identical random variables was constructed and is described in this paper. The object of the latter is to give an example of analysis of experimental facts, from the probabilistic point of view which becomes more and more frequent in technical problems.